Use of Electric Vehicles in Home-Health Care Routing Problems: Analysis of a Multi-objective Approach under Uncertainty. Issue 2 (2021) - Bahri, Oumayma; Talbi, El-Ghazali; Amodeo, Lionel
Abstract: Our aim in this study is to propose a novel approach for optimizing a variant of the home health care routing problem, in which the health-care workers perform a requested number of visits to patients by using electric vehicles. Our approach on the one hand uses multi-objective optimization methods to find optimal planning routes of EVs and on the other hand deals with uncertainty in some major problem constraints. The goal is to help decision makers choosing appropriate routes; while minimising the cost of electric vehicular displacements in terms of: the total travel cost for all home-health workers and the waiting time for all patients. Moreover, we consider in our problem the fuzzy nature of some major constraints.